STAGES OF FORMATION OF THE REGULATORY SYSTEM OF THE INTANGIBLE ASSETS MARKET - YEREMENKO, Andriy (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article substantiates the significance of the level of intellectualization of labor in terms of increasing its competitiveness, which necessitates the adaptation of the modern concept of intangible assets to the conditions of the global environment. The concept and essence of intangible assets and intellectual property are analyzed. Three important stages of the history and evolution of intellectual property are studied and highlighted, which are known respectively under the names of privileges, national patents and copyright, as well as internationalization. In particular, intellectual property objects in the WTO regulatory system in accordance with the TRIPS Agreement are studied. The author pays special attention to the need to protect intellectual property through international conventions, the oldest of which are the Paris Convention for the Protection of Industrial Property and the Berne Convention for the Protection of Literary and Artistic Works, which have been repeatedly revised and supplemented over time.Copyright grants authors and other creators of intellectual products certain rights that allow them to allow or prohibit certain types of use of their works for a limited period of time. Copyright also includes provisions on the protection of related rights relating to performances by performers, phonograms, videograms and broadcast programs. The term “industrial property” is rather conditional. We are not talking about traditional objects of industrial production, but exclusively about such objects as patents for inventions, utility models, industrial designs, trademarks, brand names, geographical indications of origin of goods, etc. The use of the term “industrial property” is explained by the fact that the listed objects are evaluated in terms of their industrial significance, economic efficiency, and profit from their use in production activities. The author of the article analyzed and structured five historical stages of the formation of the system of regulation of the market of intangible assets in accordance with the key factors of the development of the world economy.
Keywords: intangible assets; intellectual property; intellectualization; innovation; industrial property; copyright; internationalization